2021
DOI: 10.2298/yjor200125011k
|View full text |Cite
|
Sign up to set email alerts
|

An inventory system for varying decaying medicinal products in healthcare trade

Abstract: This paper introduces an inventory system for declining medicinal products under the effect of ination with price-sensitive demand. Usually, pharmaceutical inventory systems assume the deteriorating rate as constant, which is insignificant and illogical because healthcare products medicines and drugs deteriorate significantly. Thus, the deteriorating rate of medicinal products is supposed to be time-dependent and to follow three-parameter Weibull distribution. The lack of commodities is permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This assumption makes the model applicable to many deteriorating products because as the holding time of drugs increases, the percentage of deteriorated drugs increases. This assumption and the type of model utilized have been claimed to be more significant and logical than a constant rate in healthcare systems (Kumar & Kumar, 2021 ). The distributors are responsible for determining the policy of the distributors-pharmacies model.…”
Section: The Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption makes the model applicable to many deteriorating products because as the holding time of drugs increases, the percentage of deteriorated drugs increases. This assumption and the type of model utilized have been claimed to be more significant and logical than a constant rate in healthcare systems (Kumar & Kumar, 2021 ). The distributors are responsible for determining the policy of the distributors-pharmacies model.…”
Section: The Proposed Modelmentioning
confidence: 99%
“…Another audit in the same year showed that pharmaceutical companies had about $2.05 billion worth of medicines with expired dates. Issues such as incorrect prescription of drugs (Afanasjeva & Gruenberg, 2019 ) and problems related to drug inventory control, such as over-ordering drugs (Kumar & Kumar, 2021 ), have exacerbated this challenge, especially in distributors and pharmacies, which are the downstream echelons of the PSC. These pieces of evidence suggest that considering deterioration in the PSC models is of much significance (Zandkarimkhani et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Abdul Halim et al [13] studied inventory model with an overtime production opportunity for deteriorating items. K. Kumar et al [14] proposed an inventory model for healthcare medicinal products with deterioration rate following three parameter Weibull distribution under the inflation and partial backlogging. Barman et al [15] analysed optimal production policy for supply chain model with two levels for deteriorating products considering both cases, with and without shortage.…”
Section: Introductionmentioning
confidence: 99%
“…The model has distinctive design due to probabilistic deterioration. K. Kumar et al [14] formulated an inventory model where demand is time dependent and ordering cost is function of time as well, where trapezoidal fuzzy numbers are used and partial backlogging are allowed for deteriorating items. S. Kumar [25] developed a production inventory model with exponential time dependent demand under fuzzy environment and shortages are partially backlogged.…”
Section: Introductionmentioning
confidence: 99%